(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
Le sfide attuali del patrimonio religioso spagnolo ABSTRACT: Historical and artistic heritage is an essential element of a country’s culture, and in Spain it is also an important economic and tourist asset. A large percentage of the historical and artistic heritage belongs to the Catholic Church. State legislation on cultural heritage does not provide for a differentiated regime for ecclesiastical heritage, which nevertheless poses unique challenges. This article analyses some of the main challenges facing the Spanish ecclesiastical heritage in the light of the current legislation: the definition of the categories of property protected by the regulations, the distribution of powers between the State and the Regions, the harmonisation of religious and cultural use, and the financing of the necessary actions for the conservation, dissemination and promotion of the historical and artistic heritage. SUMMARY: Introduction - 1. Background and current situation - 1.1 Background - 1.2. Regulation - 1.3 Competence - 2. Composition of the heritage - 2.1. Assets and their types - 2.2 Particular categories - 3. Protection of the heritage. 3.1 - Responsibility - 3.2. Actions - 3.3. Criminal protection and administrative sanctions - 4. Religious and cultural interplay - 4.1 Harmonization of religious and non-religious uses - 4.2 Tourist and study visits – 5. Funding of the heritage - 5.1. Public sources - 5.2 Private sources - 6. Conclusions.